Evaluation of social studies for the sixth grade in the light of indicators of sustainable development. - عبد الجبار غيدان, أحمد (Journal of College of Education, 2021)
This research aims to evaluate the sociology textbook for the sixth grade in view of sustainable development indicators, by answering the question:What are the availability of indicators of sustainable development in the social textbook for the sixth grade of primary?To achieve this goal: the descriptive (analytical) approach was adopted, the research community is limited to the book of social studies for the sixth grade of primary school in Iraq for the academic year (2018-2019).The researcher adopted sustainable development indicators that were prepared by the researcher (Al-Mandalawi, 2015).To ensure the validity of the tool, which is consists of (56) standard items within three indicators: (social, economic, and environmental), it was presented to a group of experts and specialists in field of educational and psychological sciences, After which the tool was applied, and it was statistically treated using the arithmetic mean, percentages, and the Pearson correlation coefficient.
Keywords: : calendar, social book, sustainable development indicators